Literature in contemporary foreign language school textbooks in Russia: Content, approaches, and readability. (September 2022) - Calafato, Raees; Gudim, Freda
In light of the growing importance placed by states on the use of authentic materials in foreign language education programs, this study explored the literary content found in the 18 English, French, and German ministry-approved language textbooks used in upper-secondary schools in Russia. The study identified 150 literary texts, following which it compared how English, French, and German textbooks differed in their approaches to incorporating literature. The findings indicate significant differences between textbooks across languages, as well as some similarities. The study discusses the implications of the findings for learner achievement and motivation, and offers recommendations regarding what can be done to incorporate literature in ways that can deepen learner interest and engagement.